Medical image fusion based on local Laplacian decomposition and iterative joint filter. Issue 5 (9th February 2022) - Li, Weisheng; Chao, Feifei; Wang, Guofen; Fu, Jun; Peng, Xiuxiu
Abstract: Previous multi‐modal medical image fusion methods have suffered from color distortion, blurring, and noise. To address these problems, we propose a method for integrating the information contained in functional and anatomical medical images. In the proposed method, multi‐scale image representation of input images is produced by local Laplacian filtering. The rgb2ycbcr algorithm and iterative joint filters are then used to produce fused approximate images. The residual images are divided into regions of interest and noninterest regions, and then a local energy maximization scheme and local energy average scheme are used to combine these regions. Fused interest areas and fused noninterest areas are combined to produce fused residual images. Finally, an inverse local Laplacian filter is used as a reconstruction tool to produce a fused image. Experimental results indicated that our method has a distinct advantage over existing state‐of‐the‐art algorithms in terms of vision quality and objective metrics.